2014
DOI: 10.2337/dc14-0845
|View full text |Cite
|
Sign up to set email alerts
|

A Very Low-Carbohydrate, Low–Saturated Fat Diet for Type 2 Diabetes Management: A Randomized Trial

Abstract: OBJECTIVETo comprehensively compare the effects of a very low-carbohydrate, highunsaturated/low-saturated fat diet (LC) with those of a high-unrefined carbohydrate, low-fat diet (HC) on glycemic control and cardiovascular disease (CVD) risk factors in type 2 diabetes (T2DM). RESEARCH DESIGN AND METHODSObese adults (n = 115, BMI 34.4 6 4.2 kg/m 2 , age 58 6 7 years) with T2DM were randomized to a hypocaloric LC diet (14% carbohydrate [<50 g/day], 28% protein, and 58% fat [<10% saturated fat]) or an energy-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
5
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(221 citation statements)
references
References 46 publications
9
200
5
7
Order By: Relevance
“…However, a common message is that high carbohydrate intake (>50%) does not favorably affect TG and HDL in patients with diabetes. A benefit of low-carb versus low-fat diets has also been reported in other studies regarding HDL levels [40,43,48,56], TC/HDL ratio [27,56], and triglycerides [27,43,48,56].…”
Section: Step 4: Does the Patient Have A Disturbed Lipid Profile?mentioning
confidence: 57%
See 1 more Smart Citation
“…However, a common message is that high carbohydrate intake (>50%) does not favorably affect TG and HDL in patients with diabetes. A benefit of low-carb versus low-fat diets has also been reported in other studies regarding HDL levels [40,43,48,56], TC/HDL ratio [27,56], and triglycerides [27,43,48,56].…”
Section: Step 4: Does the Patient Have A Disturbed Lipid Profile?mentioning
confidence: 57%
“…Consistently with the aforementioned results, most RCTs in patients with diabetes have reported that a greater reduction in HbA1c levels is achieved after carbohydrate restriction rather than after protein or lipid restriction. Specifically, significant reductions in HbA1c have been detected at 3 and 6 months using very low-carb or low-carb diets versus lowfat diets [47][48][49], even when there was no upper limit for SFA intake [44]. Similarly, Elhanyay et al found that a low-carb MD produced a greater improvement in HbA1c than a traditional MD or a low-fat diet at 1 year [43], whereas studies comparing diets with ≥40% carb percentage, differing mainly in protein and lipid content, have reported similar reduction rates of HbA1c at 1 year [42,45,50].…”
Section: Step 2: Does the Patient Have High Hba1c?mentioning
confidence: 99%
“…Take meal plan, for example. How meal composition affects glycaemia, satiety and weight management is well documented in the literature [2][3][4][5][6][7][8][9][10][11][12][13][14] and in the official guidelines from diabetes organizations [15]. Balancing the meals by adding lean protein, extra fiber, healthy fat and vegetables has consistently shown glycaemia benefits.…”
Section: Introductionmentioning
confidence: 99%
“…43 Recently, Tay et al reported on a randomized controlled study investigating hypocaloric low carbohydrate versus high carbohydrate diets over 24 weeks and 1 year, respectively, in obese adults with T2DM. 44,45 Saturated fat intake was limited to ,10% despite total fat intake being 58% and carbohydrate 14% of the total energy intake in the low carbohydrate group. Intensive dietary counseling and a physical activity plan were included.…”
Section: Glycemic Controlmentioning
confidence: 99%
“…36 Of concern are recent data suggesting that increasing LDL cholesterol in the Atkins diet may have detrimental effects on vascular function. 44 Additionally, it is questionable whether the increase in HDL provides any meaningful benefit, further compounding the adverse effect of a VLCD in obesity and T2DM. However, these adverse effects may be overcome.…”
mentioning
confidence: 99%